1996
DOI: 10.1183/09031936.96.09081624
|View full text |Cite
|
Sign up to set email alerts
|

Female gender as a determinant of cough threshold to inhaled capsaicin

Abstract: Chronic, nonproductive cough and cough associated with the use of angiotensin converting enzyme inhibitors, are more frequently observed in females as compared to males.To examine the influence of sex, age, height, weight and pulmonary function on airway cough sensitivity, cough threshold to inhaled capsaicin, an index of the airway cough sensitivity, was measured in 160 nonsmoking, nonatopic healthy subjects. Forty young males (aged 24±2 yrs) 40 young females (aged 22±2 yrs) 40 middle-aged males (aged 48±5 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
108
5
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 19 publications
15
108
5
3
Order By: Relevance
“…WAGNER et al [28] also showed a strong correlation between increase in peripheral resistance and degree of bronchial hyperresponsiveness to methacholine. Interestingly, studies have shown a higher smoke-related bronchial hyperresponsiveness in females compared with males [3] and lower cough threshold in females than males when they were exposed to cough stimuli (capsaicin) [29]. Further measurements of bronchial hyperresponsiveness in population-based studies might clarify this.…”
Section: Tobacco Smoking and Respiratory Symptomsmentioning
confidence: 98%
“…WAGNER et al [28] also showed a strong correlation between increase in peripheral resistance and degree of bronchial hyperresponsiveness to methacholine. Interestingly, studies have shown a higher smoke-related bronchial hyperresponsiveness in females compared with males [3] and lower cough threshold in females than males when they were exposed to cough stimuli (capsaicin) [29]. Further measurements of bronchial hyperresponsiveness in population-based studies might clarify this.…”
Section: Tobacco Smoking and Respiratory Symptomsmentioning
confidence: 98%
“…With this technique, capsaicin concentrations (or other tussives such as citric acid and distilled water) are doubled until two and five "cough events" (typically defined by the number of expulsive events, or "cough sounds") are achieved, representing the threshold and suprathreshold response, respectively. These studies have shown differences in the cough response between ages [13], genders [14][15][16] and diseases [4,5,13,17]. However, these data cannot infer changes in expiratory muscle activation, duration of expulsive phases and the airflow dynamics with increasing capsaicin concentration, all which are essential components in defining the cough response.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy women have a more sensitive cough reflex than do healthy men [8,9], and women with chronic cough demonstrate an enhanced cough reflex compared with their male counterparts [10]. In terms of health-related quality of life, women are significantly more adversely affected by chronic cough than are men [11].…”
mentioning
confidence: 99%